2015
DOI: 10.1371/journal.pone.0139521
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Zebrafish Locomotor Response

Abstract: Zebrafish larvae display rich locomotor behaviour upon external stimulation. The movement can be simultaneously tracked from many larvae arranged in multi-well plates. The resulting time-series locomotor data have been used to reveal new insights into neurobiology and pharmacology. However, the data are of large scale, and the corresponding locomotor behavior is affected by multiple factors. These issues pose a statistical challenge for comparing larval activities. To address this gap, this study has analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 28 publications
1
69
0
1
Order By: Relevance
“…However, one should be aware that such observation is only valid provided that the sensory context remains relatively stable. Hence for instance, a prolonged uniform drop in luminosity is known to enhance the overall motor activity (generally measured by displacement over a period of time) for up to several tens of minutes ( Prober et al, 2006 ; Emran et al, 2007 , 2009 ; Liu et al, 2015) . This long-term behavioral change, so-called photokinesis, might be regulated by deep brain photoreceptors ( Fernandes et al, 2013 ; Horstick et al, 2017) and thus constitutes a distinct mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…However, one should be aware that such observation is only valid provided that the sensory context remains relatively stable. Hence for instance, a prolonged uniform drop in luminosity is known to enhance the overall motor activity (generally measured by displacement over a period of time) for up to several tens of minutes ( Prober et al, 2006 ; Emran et al, 2007 , 2009 ; Liu et al, 2015) . This long-term behavioral change, so-called photokinesis, might be regulated by deep brain photoreceptors ( Fernandes et al, 2013 ; Horstick et al, 2017) and thus constitutes a distinct mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the strain might influence locomotor activity of zebrafish. Similarly, Liu et al [73] reported behavioral differences of strains (TL, TLAB and AB) when measuring locomotion during abrupt changes in light cycles. Strain differences were also found in a study on survival and neurocranial effects of ethanol [75].…”
Section: Zebrafish Strainmentioning
confidence: 92%
“…Zebrafish have emerged as a model for neurodevelopmental disorders (59) and behavioral assays for seizure (60) and motor deficits (61) have been described. Therefore, we characterized the locomotion of hcfc1a mutants in response to light stimulus (62). Our results using Zebrabox technology demonstrated reduced motility as indicated by distance travelled without defects in overall speed.…”
Section: Discussionmentioning
confidence: 92%